Penggunaan Teknik Pertanyaan Bimbingan untuk Meningkatkan Pencapaian Menulis Teks Recount Siswa - akhmad hidayat (Mastery: Master of English Language Journal, 2023)
The research is conducted to find the answer of the problem how the use of guiding questions technique can improve students’ writing recount text achievement in the first grade of science of Al Misri Islamic Senior High School Curahmalang, Rambipuji. The research design is classroom action research. This research is covered four stages of activities; they are planning of the action, implementing of the action, observing, and reflecting of the action. Based on the result of writing test in cycle one showed that the percentage of the students who got score 7,65 was 60%. And in cycle two, it improved to be 37%. In addition, the average result of the students’ active participation was 65% in cycle one. In cycle two, the average result of the students’ active participation indicated improvement that was 75%. It can be concluded that the action in cycle two was successful. Finally, it can be the use of guiding questions technique could improve the first grade of science students’ writing recount text achievement and could improve the first grade of science students’ active participation in teaching learning process at Al Misri Islamic Senior High School Curahmalang, Rambipuji.